Analisis Prioritas Strategi Industri Kreatif Fesyen Batik Menghadapi Masyarakat Ekonomi Asean (Mea) Dengan Metode Swot Dan Ahp - Arisanti, Shinta (2016)
Indonesia is currently the ASEAN Economic Community (AEC), so the government needs to prepare to formulate strategic steps, especially in the Small and Medium Enterprise (SME) creative industries. Given a lot of creative industries SME batik fashion art one of them in Sub Sondakan Laweyan District of Surakarta. Village of Sondakan is one central hub that is already known batik production in Surakarta. Although the production process is still traditionally many good quality products produced. With fashion's creative industries batiknya Village Sondakan certainly very likely to participate once in the MEA, thus the need for cooperation between SMEs step strategy Batik, private entrepreneurs and the role of government. This study aims to delve into the issues MEA information and analyzes on the readiness of the creative industries in Sub Sondakan. Also in this study using the SWOT method to determine the readiness and obtain the necessary strategies in Sub Sondakan Batik SMEs, as well as obtaining the necessary strategic priority IKM Batik with AHP method. The results in this study indicate that the position of SMEs in the Village Sondakan Batik is a moderately attractive which is defined as a growth strategy through horizontal integration, namely activities to develop SME Batik through mutual cooperation between SMEs Batik, private businesses and the government. Where the results indicate that strategy WT priority that the activities of a defensive nature are very influential in the development of such facilities improve and strengthen human resource limitations SME marketing Batik creative industries there is the Village Sondakan Laweyan District of Surakarta